CHANGES IN THE LEVEL OF SOCIO-ECONOMIC DEVELOPMENT IN WESTERN BALKAN EU ACCESSIONIST COUNTRIES IN 2010-2018 - Kozak, Sylwester; Muça, Etleva (Zeszyty Naukowe UPH seria Administracja i Zarządzanie, 2021)
The paper presents the results of research on changes in the level of socioeconomic development in Western Balkan countries, including Albania, Montenegro, North Macedonia and Serbia, for the period 2010- -2018. The level of development was determined by the method TOPSIS, based on two social and six economic criteria using data from national statistical offices. The results indicate that four countries present long-term positive growth over the course of the decade. Throughout the entire analyzed period, Montenegro characterized with the highest and Albania the lowest development in the region. These countries characterized with the most and the least favorable levels of the analyzed categories, inter alia, the level of employment in agriculture, population growth, infant mortality rate, or the average wage. The levels of development of North Macedonia and Serbia were average for the region. However, the stable and rather favorable trends of the main socia